Neuromechanical adaptations during a robotic powered exoskeleton assisted walking session. (3rd September 2018) - Ramanujam, Arvind; Cirnigliaro, Christopher M.; Garbarini, Erica; Asselin, Pierre; Pilkar, Rakesh; Forrest, Gail F.
Abstract : Objective : To evaluate gait parameters and neuromuscular profiles of exoskeleton-assisted walking under Max Assist condition during a single-session for; (i) able bodied (AB) individuals walking assisted with (EXO) and without (non-EXO) a powered exoskeleton, (ii) non-ambulatory SCI individuals walking assisted with a powered exoskeleton. Design : Single-session. Setting : Motion analysis laboratory. Participants : Four AB individuals and four individuals with SCI. Interventions : Powered lower extremity exoskeleton. Outcome Measures : Temporal-spatial parameters, kinematics, walking velocity and electromyography data. Results : AB individuals in exoskeleton showed greater stance time and a significant reduction in walking velocity (P < 0.05) compared to non-EXO walking. Interestingly, when the AB individuals voluntarily assisted the exoskeleton movements, they walked with an increased velocity and lowered stance time to resemble that of slow walking. For SCI individuals, mean percent stance time was higher and walking velocity was lower compared to all AB walking conditions (P < 0.05). There was muscle activation in several lower limb muscles for SCI group. For AB individuals, there were similarities among EXO and non-EXO walking conditions however there were differences in several lower limb EMGs for phasing of muscle activation. Conclusion : The data suggests that our AB individuals experienced reduction in walking velocity and muscle activation amplitudes while walking in the exoskeleton and moreover with voluntary control there is a greater temporal-spatial response of the lower limbs. Also, there are neuromuscular phasic adaptions for both AB and SCI groups while walking in the exoskeleton that are inconsistent to non-EXO gait muscle activation.